Comparison of the effects of different nickel-titanium root canal preparation instruments in removing highly curved root canal fillings - SUN Fei; LIANG Jingping (口腔疾病防治, 2019)
Objective To compare the effects of four nickel-titanium root canal preparation instruments on removing fillings in severely curved root canals.Methods Forty single-bend resin root canals were selected to simulate curved root canals. A ProTaper Universal tool was used to prepare the canals to F2. Photographs were taken under a stereomicroscope. Photographs were then retaken after the canals were filled tightly using the hot gutta-percha continuous wave filling method. The canals were stored in a water bath at 37 ℃ and 100% humidity for 21 days. Forty processed root canal samples were randomly divided into four groups, with 10 in each group. ProTaper NEXT, Reciproc, Mtwo and Twisted File Adaptive (TFA) tools were used to remove fillings in the root canal. The time of the procedure was recorded, and photographs were taken again after the procedure was completed. The residual rate of filling materials, root canal displacement and procedure time were compared.Results The rates of remaining filling materials in the four groups were not significantly different (P > 0.05), and the amount of remaining filling material in the apical third was greater than in other parts of the canal (P < 0.05). At 1 mm (F=4.245, P=0.014), 2 mm (F=5.893, P=0.003), 3 mm (F=2.969, P=0.049), 6 mm (F=7.447, P=0.001) and 8 mm (F=3.567, P=0.027) from the apical point, the transportation of the Mtwo group was significantly greater than that in the other three groups. At the 4 mm from the apical point, the transportation of the Mtwo group was significantly greater than that in the ProTaper NEXT and TFA groups (P < 0.05). At the 5 mm from the apical point, the transportation of the Mtwo group was significantly greater than that of the TFA group (P < 0.05). The procedure times of the four experimental groups were not significantly different (F=0.925, P=0.44).Conclusion Four types of nickel-titanium root canal preparatory instruments can be used to remove fillings in severely curved root canals; the root canal deviations caused by the ProTaper NEXT, Reciproc and TFA instruments are different, but these tool can all be used in the treatment of curved root canals. None of the four instruments could completely remove the filling materials from the root canals, and the residual rate was highest for fillings in the apical third. Therefore, it is necessary to use other instruments or methods to further clean root canal fillings.